Gender Aware Therapy Based on Mubadalah for Family Resilience Pasca Domestic Violence - Farmawati, Cintami; Carland, Susan; Razak, Marini (Journal of Sufism and Psychotherapy, 2024)
This research is motivated by the phenomenon of widespread domestic violence which has an impact on failure in the family and psychological problems faced by children. Domestic violence is showing an alarming increase and has an impact on the loss of family unity, so it is necessary to have family functioning in facing difficulties to maintain family integrity after domestic violence. The aim of the research is to find out how mubjadi-based gender aware therapy works for family resilience after domestic violence. This research is qualitative research. The subjects in the research were one family after domestic violence. Data collection methods use interviews, observation and documentation. The data analysis used is data reduction, data presentation, and drawing conclusions. The research results show that family resilience after domestic violence can be seen from key family processes for adapting to situations after domestic violence. Key family processes involve three components, namely belief systems, family organization patterns, and communication processes. Meanwhile, mubjadi-based gender aware therapy for family resilience is implemented through the stages of problem conceptualization, counseling intervention and termination. In counseling interventions, how to get along between husband and wife in a good way (husnu al mu'asyarah), letting each other go (at taradhi), discussing to reach an agreement (al musyawarah), helping each other (at taawun), and understanding each other is practiced. each other (husnu at tafahum).